INFANT HEALTH PRODUCTION FUNCTION: ROLE OF PRENATAL CARE - Heni Wahyuni (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This article reviews the economic concept of the health production function regarding the determinants of infant health and the results of previous empirical studies on the role of prenatal care in infant health production. The review will include a brief explanation about the health production function, followed by how the concept applies to infant health, explaining the derivation of the infant health production function, and finally the previous empirical studies on the role of prenatal care in infant health production. Grossman’s model on the demand for health and the framework of the infant health production function of Rosenzweig and Schultz explain that the following important factors will influence infant health and the demand for maternal medical care: age, wage/income, education, and knowledge. Furthermore, given that an infant inherits its health capital stock from its mother, there may be biological factors (e.g., a specific health endowment) that may be keys to determining infant health. In terms of the role of prenatal care, the review summaries that there is strong evidence that prenatal care does affect infant health. However, it is difficult to isolate the causal effect between the two without con-trolling for endogeneity, such as via a natural experiment. It is possible that there are unob-served heterogeneous factors of mothers that can affect prenatal care and infant health. Many studies have attempted to estimate the infant health production function, taking into account these selection biases. The merits and critiques of existing methods have also been discussed in the previously mentioned studies, which have mostly been conducted in relation to developed countries and have very rarely been conducted for the developing countries’ context. The find-ings of this review state that studies into this topic should consider many important aspects, such as selectivity bias, the determinants of infant health as stated in theory and previous empirical studies, and the need to use an appropriate measurement of adequate prenatal care, especially for the case of developing countries.Keywords: health production function, infant health production function, Grossman model, prenatal care